Teachers‟ Roles in Promoting Students‟ Use of Cognitive Capacities and Strategies - Mazri, Meriem; Boudehane, Nora (University of Eloued جامعة الوادي, 2016)
Cognitive structures are the basic mental processes people use to make sense of information. In a language classroom setting, learners use those mental processes to understand academic content and create output that reflects what has been perceived and learnt. However,one issue teachers can ecounter is that when they present a very well organized, suitable lesson, they wonder why some learners ‗get it‘ and others do not.In effect, in order for language learners to be proficient , teachers can help them develop their intellectual capacity so they can meet the academic experience with success. To fulfill this aim, students need cognitive strategies to fully understand and construct meaning from their experiences. Hence, the purpose of the present paper is to shed some light on teachers‘ perspectives, standpoints and ways they adoptd to help students foster their cognitive capacities when learning a foreign language at the depatment of Letters and English Language, University of Frères Metouri Constantine. The analysis of the teachers questionnaire yielded valuable information obout different issues connected to instruction, learning and learners cognitive capacities. These information would help us understand better the teaching learning processes and so offer possible solutions and recommandations for future use.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Teachers, Roles in Promoting Students, Cognitive Capacities, Strategies